Indonesian Cinnamon (Cinnamomum burmanni (Nees & T. Nees) Blume) as Promising Medicinal Resources: A Review - Handayani, Aisyah; Lailaty, Intani Quarta; Rosyidah, A'liyatur; Sari, Dewi Ratih Tirto; Yunarto, Nanang; Suherman, Dadang (Jurnal Sylva Lestari, 2024)
Cinnamomum burmanni (Lauraceae) is one of the Cinnamomum species native to Indonesia. Given the worldwide use of cinnamon, the famous spice derived from its bark, cinnamon is also considered to possess medicinal properties. Consequently, a comprehensive review of C. burmanni was conducted to explore its medicinal benefits. This paper reviews several studies on the traditional use of C. burmanni in Indonesia, its phytochemistry, and its pharmacological properties. Traditionally, C. burmanni is utilized not only as spices but also for medicinal purposes, food ingredients, and ritual purposes. The bark is the most commonly used part, while few other parts of the plant are used. Several phytochemical compounds of C. burmanni have been identified. C. burmanni also has been reported to exhibit a wide range of biological activities. From those studies, it can be concluded that the medicinal use of C. burmanni’s bark has been scientifically validated due to its rich content of active compounds. Furthermore, other parts of C. burmanni should be analyzed to determine their content of active compounds. Keywords: active compound, Cinnamomum burmanni, medicinal plant, spice, traditional medicine